2014
DOI: 10.3899/jrheum.131110
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Arterial Stiffness in Female Patients with Takayasu Arteritis

Abstract: In our cohort of female patients with TA, the disease itself and mean BP were the strongest determinants associated with arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Moreover, TAK was significantly associated with ba-PWV independently of age, blood pressure, or lipid profile. Two previous studies demonstrated that TAK is associated with higher arterial stiffness, which was measured by cf-PWV and cr-PWV (carotid-radial PWV) in one study 14) and cf-PWV in another study 15) . They have relatively small sample sizes (10 14) and 27 15) patients with TAK).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, TAK was significantly associated with ba-PWV independently of age, blood pressure, or lipid profile. Two previous studies demonstrated that TAK is associated with higher arterial stiffness, which was measured by cf-PWV and cr-PWV (carotid-radial PWV) in one study 14) and cf-PWV in another study 15) . They have relatively small sample sizes (10 14) and 27 15) patients with TAK).…”
Section: Discussionmentioning
confidence: 96%
“…Two previous studies demonstrated that TAK is associated with higher arterial stiffness, which was measured by cf-PWV and cr-PWV (carotid-radial PWV) in one study 14) and cf-PWV in another study 15) . They have relatively small sample sizes (10 14) and 27 15) patients with TAK). The arterial stiffness was demonstrated higher in patients with TAK comparing with normal controls, and it did not correlate with ESR or CRP.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations